Accelerated whole breast irradiation in early breast cancer patients with adverse prognostic features - Lee, Sea-Won (Oncotarget, 2016)
PURPOSE: Accelerated whole breast irradiation (AWBI) and conventional whole breast irradiation (CWBI) were compared to determine whether AWBI is as effective as CWBI in patients with early breast cancer and adverse prognostic features. PATIENTS AND METHODS: We included 330 patients who underwent breast-conserving surgery (BCS) and post-operative radiation therapy (RT) using AWBI for pT1-2 and pN0-1a breast cancer from 2007 to 2010. These patients were matched with 330 patients who received CWBI according to stage, age (±3 years), and the year of BCS. AWBI of 39 Gy and CWBI of 50.4 Gy were given in 13 and 28 fractions, respectively. RESULTS: Median follow-up time was 81.9 months. There were no statistically significant differences between the AWBI and CWBI groups in terms of age, stage, tumor grade, or molecular subtype. More patients with Ki-67 index ≥ 14% were present in the AWBI group (AWBI 47.0% vs. CWBI 10.3%; P<0.01). The 5-year ipsilateral breast tumor relapse (IBTR) rates for the AWBI and CWBI groups were 0.8% and 1.8%, respectively (P=0.54). High tumor grade was a statistically significant risk factor for IBTR (5-year IBTR rate: 2.9%; P=0.01). Ki-67 ≥ 14% was marginally related to IBTR (5-year IBTR rate: 2.2%; P=0.07). There were no statistically significant differences in the hazard ratios between the AWBI and CWBI groups according to any of the risk factors. There were no acute grade 3 toxicities in the AWBI group. There were no late grade 3 toxicities in either group. CONCLUSIONS: AWBI is comparable to CWBI in early breast cancer with adverse prognostic features.